Developing Competitive Business Intelligence for Islamic Digital Banking: A Multi-Dimensional Customer Review Analytics - Asep Koswara; Muhammad Irfan; Nila Nopianti; Rifki Harsono (LP3M Universitas Putra Bangsa, 2026)
Intensifying competition in Islamic digital banking requires financial institutions to continuously monitor customer experiences and transform them into strategic business intelligence. However, existing evaluation approaches largely rely on isolated indicators, such as application ratings or customer satisfaction, which provide limited insights for competitive benchmarking. This study proposes a Competitive Business Intelligence (CBI) framework to evaluate the competitive performance of Islamic digital banking applications in Indonesia by integrating multidimensional customer review analytics. Using 7,424 Google Play Store reviews from four Islamic digital banking applications, the study identifies key competitive strengths, service weaknesses, and strategic priorities from customers' perspectives. The results indicate that one application consistently demonstrated superior competitive performance, while authentication and login issues represent the most critical barrier to customer experience across applications. Furthermore, digital payment services consistently emerge as the primary competitive strength. The proposed Competitive Business Intelligence Index (CBII) offers a multidimensional benchmarking tool that supports evidence-based strategic decision-making, service innovation, and competitive positioning. This study contributes a practical business intelligence framework that enables Islamic digital banks to leverage customer feedback as a strategic resource for sustainable competitive advantage.